Influence of metallic and basic sites of Ni-promoted SBA-15 on the mechanistic path of CO2-methanation - Setiabudi, Herma Dina; Triwahyono, Sugeng; Vo, Dai Viet N.; Nurul Aini, Mohamed Razali (2018)
The utilization of carbon dioxide (CO2) has become an important topic in recent years. As CO2 is one of the main contributors to greenhouse effect and hence to climate change, there is a growing interest in its use as a feedstock in chemical processes. The conversion of CO2 into methane (CH4) has been investigated extensively, using variety of supported metal catalysts including Ni/SBA-15. However, proper design of catalyst preparation is needed to prepare well-dispersed Ni/SBA-15. In addition, the real function of metal and basic sites on the CO2 methanation process over Ni/SBA-15 is still unclear. Therefore, the objective of this study is to synthesis the well-dispersed Ni/SBA-15 for CO2 methanation and investigates the influence of metallic and basic sites of Ni/SBA-15 on the mechanistic path of CO2 methanation. The well-dispersed Ni/SBA-15 were synthesized by studying the effect of TEOS/P123 mass ratios (R1.5, R2.21, R3.0), hydrothermal techniques (Reflux (R) and Teflon (T)) and Ni content (1 – 10 wt%). The properties of Ni/ SBA-15 were determined by XRD, BET, FTIR, TEM, FESEM-EDX, H2-TPR. The CO2 methanation were carried out in a stainless steel fixed-bed reactor and the role of metallic and basic sites on mechanistic path of CO2 methanation were clarified using in-situ FTIR adsorbed pyrrole, H2, CO2 and H2 + CO2. The results revealed that the well-dispersed Ni/SBA-15 was successfully synthesized at TEOS/P123 = 2.21, reflux hydrothermal technique and 5 wt.% Ni, with CO2 conversion = 99.7% and CH4 yield = 98.2% at T = 673 K. The in-situ FTIR studies of adsorbed H2, CO2, and H2 + CO2 confirmed that the CO2 methanation of Ni/SBA-15 proceeded by CO dissociative reaction pathway. Firstly, the CO2 and H2 molecule were dissociated to CO, O, and H atoms on the surface of Ni metal active sites and spillover onto the support to form unidentate carbonates, bidentate carbonates and linear carbonyl as the main adsorption species. Then, these intermediate species were further undergoing hydrogenation with the atomic hydrogen to form CH4 and H2O. In conclusion, well dispersed Ni/SBA-15 was successfully synthesized and the role of metallic and basic sites of Ni/SBA-15 on CO2 methanation were successfully discovered. The metal sites were responsible in the dissociation of CO2 and H2, while the concentration of basic sites influenced the CO2 adsorption ability of the catalyst.